2020
DOI: 10.1038/s41467-020-15106-1
|View full text |Cite
|
Sign up to set email alerts
|

TRIM5α self-assembly and compartmentalization of the HIV-1 viral capsid

Abstract: The tripartite-motif protein, TRIM5α, is an innate immune sensor that potently restricts retrovirus infection by binding to human immunodeficiency virus capsids. Higher-ordered oligomerization of this protein forms hexagonally patterned structures that wrap around the viral capsid, despite an anomalously low affinity for the capsid protein (CA). Several studies suggest TRIM5α oligomerizes into a lattice with a symmetry and spacing that matches the underlying capsid, to compensate for the weak affinity, yet lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 64 publications
(93 reference statements)
1
49
0
Order By: Relevance
“…It is of note to recognize that the pathways discussed characterize the binding of IP 6 to preformed mature capsid complexes and not the molecular pathways for the co-assembly of CA and IP 6 , which may differ. Further simulations that target the co-assembly of CA and IP 6 will likely require coarse-grained molecular simulation techniques to overcome the long time scale barriers associated with biomolecular assembly phenomena ( 43 , 44 ). The computed thermodynamic quantities, however, are state functions that do not change in response to the particular path taken, so the IP 6 interactions revealed by the ligand density maps are therefore general.…”
Section: Discussionmentioning
confidence: 99%
“…It is of note to recognize that the pathways discussed characterize the binding of IP 6 to preformed mature capsid complexes and not the molecular pathways for the co-assembly of CA and IP 6 , which may differ. Further simulations that target the co-assembly of CA and IP 6 will likely require coarse-grained molecular simulation techniques to overcome the long time scale barriers associated with biomolecular assembly phenomena ( 43 , 44 ). The computed thermodynamic quantities, however, are state functions that do not change in response to the particular path taken, so the IP 6 interactions revealed by the ligand density maps are therefore general.…”
Section: Discussionmentioning
confidence: 99%
“…Biomolecule self-assembling is highly implicated in various biologic events through a variety of non-covalent interactions, such as hydrophobic interaction, hydrogen bonds, electrostatic interaction, and metal coordination (Bera et al, 2020;Yu et al, 2020). The self-assembly structures are the basis of forming different complex biological structures (Cao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For TRIM5, both dimeric Diaz-Griffero et al, 2009) and trimeric Wagner et al, 2016Wagner et al, , 2018 assemblies have been observed via the same interface, suggesting plasticity of the oligomer formed by the Bbox domain. Molecular-dynamics simulations suggest that both oligomers are present during binding to the HIV capsid (Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%